Pelatihan Teknik Asertivitas untuk Meningkatkan Self-Esteem Korban Bullying - Amalia Hana Firdausi; Maria Goretti Adiyanti (Faculty of Psychology, Universitas Gadjah Mada, 2016)
The purpose of this study is to examine the effect of assertiveness techniquestraining to improve bullying victims’ self-esteem. This study was a quasi experiment withuntreated control group with pre-test and double post-test design. The data werecollected by using adaptation instrument of Peer Interactions in Primary School (PIPS)Questionnaire, assertiveness scale, and self-esteem scale. The subjects were 18 students in4 th -5 th grade who are indicated as bullying victims and have self-esteem scores categorizedin low to moderate levels (8 students in experimental group and 10 students in controlgroup). The result of the Mann Whitney U test showed that there was no difference inself-esteem scores between the experimental and control group during the pretest (p >0.05). After being treated, the differences in self-esteem scores were significant with Z = -3.113; p = 0.002 (p < 0,01) between the experimental group and control group, in which themean score of self-esteem in the experimental group was higher than the control group